Robotic partial nephrectomy in the pediatric population: Cumulative experience at a large pediatric hospital. Issue 4 (August 2022) - Antar, Ali; Bachtel, Hannah Agard; Bates, Jenna N.; Kim, Soo Jeong; Saleem, Asad; Bhatia, Vinaya; Link, Richard E.; Koh, Chester J.
Summary: Introduction: Robotic partial nephrectomy is a complex minimally invasive procedure that addresses the intricate anatomy of renal masses while maximizing preservation of renal function. However, while common in adults, the evolution toward these minimally invasive procedures for children has been slow due to the anticipated technical difficulties in pediatric-sized working spaces. We present our technique and our experience with pediatric robotic partial nephrectomies that were performed with our adult urology colleagues at a large free-standing children's hospital. Methods: The video describes our technique for a robotic right-sided partial nephrectomy in a 14-month-old male patient. The video highlights several steps of the procedure including positioning and port placement, tumor resection, and renorrhaphy. Results: Six pediatric patients underwent robotic partial nephrectomy with our associated adult urologic surgeons from January 2019 to January 2021. The surgical pathology revealed both benign as well as malignant diagnoses. Conclusion: Robotic partial nephrectomy is a feasible minimally invasive procedure in children. The collaboration with adult minimally invasive urologic surgeons with extensive adult procedural experience is recommended to avoid potential complications with this technically challenging procedure in pediatric patients. Pediatric strategies for robotic port placement are often needed to accommodate the smaller size of pediatric patients as well as tumor size.